2014
DOI: 10.2174/1874210601408010148
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Ridge Augmentation with Titanium Mesh. A Retrospective Clinical Study

Abstract: An adequate amount of bone all around the implant surface is essential in order to obtain long-term success of implant restoration. Several techniques have been described to augment alveolar bone volume in critical clinical situations, including guided bone regeneration, based on the use of barrier membranes to prevent ingrowth of the epithelial and gingival connective tissue cells. To achieve this goal, the use of barriers made of titanium micromesh has been advocated.A total of 13 patients were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 38 publications
(45 reference statements)
1
58
0
3
Order By: Relevance
“…The use of titanium for GBR was inspired from a successful outcome of using a titanium mesh for reconstruction of maxillofacial defects . Several studies have shown that using a titanium mesh alone or with bone substitutes is an effective procedure for localized alveolar ridge augmentation prior to, or simultaneously with, implant placement . Occlusive titanium and micro‐perforated titanium membrane have also been introduced and used for treatment of peri‐implant bone defects and ridge augmentation .…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%
“…The use of titanium for GBR was inspired from a successful outcome of using a titanium mesh for reconstruction of maxillofacial defects . Several studies have shown that using a titanium mesh alone or with bone substitutes is an effective procedure for localized alveolar ridge augmentation prior to, or simultaneously with, implant placement . Occlusive titanium and micro‐perforated titanium membrane have also been introduced and used for treatment of peri‐implant bone defects and ridge augmentation .…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%
“…For example, Herford et al found that addition of recombinant human bone morphogenetic protein type 2 to a collagen matrix, which is applied during distraction osteogeneis, increases faster bone tissue regeneration [5]. Poli et al also reported that guided BTE, using titanium micromesh filled with bone grafts, provides sufficient bone volume correction in humans with severe alveolar atrophies [6]. Furthermore, clinical study by Chen et al found an increase of bone healing and good bone to implant incorporation when biphasic calcium phosphate ceramics were used as a local treatment for comminuted fractures and fracture nonunion [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have demonstrated that titanium meshes can promote the formation of new bone, when positioned before [19–24] or simultaneously with dental implants [2527]. …”
Section: Introductionmentioning
confidence: 99%